2016
DOI: 10.1007/s10561-016-9604-3
|View full text |Cite
|
Sign up to set email alerts
|

Kinetin improves motility, viability and antioxidative parameters of ram semen during storage at refrigerator temperature

Abstract: The present experiment was conducted to evaluate the effect of kinetin on ram semen quality during cold storage. Ejaculates were collected using an artificial vagina from five Qezel rams. Ejaculates which met the criteria (volume of 0.75-2 ml; minimum spermatozoa concentration of 2.5 × 109 spermatozoa/ml and forward progressive motility of 80%), were pooled, diluted with extender without kinetin (control) or enriched with 25 (K 25), 50 (K 50), 100 (K 100) and 200 (K 200) μM kinetin at a final concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The efficiency of TL-HEPES and PBS in sperm processing (16,17) and in short-term storage (18)(19)(20) was identified in previous studies. Tris-citrate is a commonly used extender (1), and it is also usually used as the control or main extender in ram sperm-extender studies (21)(22)(23)(24). TEST, TL-HEPES, and PBS extenders were found to be effective in protecting the sperm against cold shock when freezing rat sperm and in equilibration at 4 °C (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of TL-HEPES and PBS in sperm processing (16,17) and in short-term storage (18)(19)(20) was identified in previous studies. Tris-citrate is a commonly used extender (1), and it is also usually used as the control or main extender in ram sperm-extender studies (21)(22)(23)(24). TEST, TL-HEPES, and PBS extenders were found to be effective in protecting the sperm against cold shock when freezing rat sperm and in equilibration at 4 °C (20,25).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that ram semen enrichment with butylated hydroxytoulene, taurine, catalase, quercetin, palmitoleic acid, and kinetin enhances motility or viability compared to the control when stored as liquid at refrigerator or after freeze‐thawing process (Banday et al, ; Câmara et al, ; Eslami et al, ; Rather et al, ; Zadeh Hashem & Eslmi, ). The results of the present experiment indicated that Id at 1, 2 and 4 µM enhanced total motility, FPM, and VCL at 48 and 72 hr of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that ram semen enrichment with butylated hydroxytoulene, taurine, catalase, quercetin, palmitoleic acid, and kinetin enhances motility or viability compared to the control when stored as liquid at refrigerator or after freeze-thawing process (Banday et al, 2017;Câmara et al, 2011;Eslami et al, 2017;Rather et al, 2016;Zadeh Hashem & Eslmi, 2018 experiment. Previous study revealed a correlation between capacities of spermatozoa in fertilization with spermatozoa motility assessed by CASA (Larsen et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…As for motility, ram semen liquid storage is associated with a gradual decrease of sperm viability [46] [47] and such decrease is negatively correlated with LPO [45] and can be attributed to the endogenous production of ROS [48].…”
Section: Effect Of Liquid Storage On Sperm Parametersmentioning
confidence: 99%
“…The antioxidative properties of kinetin have been described [95]. Kinetin has been tested as an additive to ram semen extender during chilled storage up to 72 h. It was concluded that kinetin at appropriate concentrations (25 -100 µM) improves spermatozoa kinematics, viability, sperm plasma membrane functionality and antioxidative parameters [48].…”
Section: Amino Acids and Proteinsmentioning
confidence: 99%